PKHD1, the Polycystic Kidney and Hepatic Disease 1 Gene, Encodes a Novel Large Protein Containing Multiple Immunoglobulin-Like Plexin-Transcription–Factor Domains and Parallel Beta-Helix 1 Repeats - Onuchic, Luiz F. (The American Society of Human Genetics, 2002)
Autosomal recessive polycystic kidney disease (ARPKD) is a severe form of polycystic kidney disease that presents primarily in infancy and childhood and that is characterized by enlarged kidneys and congenital hepatic fibrosis. We have identified PKHD1, the gene mutated in ARPKD. PKHD1 extends over ⩾469 kb, is primarily expressed in human fetal and adult kidney, and includes a minimum of 86 exons that are variably assembled into a number of alternatively spliced transcripts. The longest continuous open reading frame encodes a 4,074-amino-acid protein, polyductin, that is predicted to have a single transmembrane (TM)-spanning domain near its carboxyl terminus, immunoglobulin-like plexin-transcription–factor domains, and parallel beta-helix 1 repeats in its amino terminus. Several transcripts encode truncated products that lack the TM and that may be secreted if translated. The PKHD1-gene products are members of a novel class of proteins that share structural features with hepatocyte growth-factor receptor and plexins and that belong to a superfamily of proteins involved in regulation of cell proliferation and of cellular adhesion and repulsion.